Perbaikan Status Gizi Balita Melalui Pendampingan Gizi Secara Intensif di Desa Singosari, Gresik: Perbaikan Status Gizi Balita Melalui Pendampingan Gizi Secara Intensif di Desa Singosari, Kabupaten Gresik - Desty Muzarofatus Sholikhah; Amalia Rahma (Amerta Nutrition, 2022)
Background: Data from the Indonesian Nutrition Status Survey in 2021 showed the prevalence of stunted in Gresik is 23%, so Gresik became one of the district-focused locations for eliminating stunting. The Gresik District Government had determined 13 villages to focus on interventions to accelerate integrated stunting prevention and control in 2022, one of which was Singosari Village. Referred to President Regulation Number 75 in 2021 about to accelerate stunting reduction, so needed intensive nutritional assistance to families at risk of stunting with improving knowledge and behavior by education of nutrition to families of toddlers in Singosari Village. Objectives: To examine the impact of intensive nutritional assistance on the nutritional status of children under five in Singosari Village, Gresik. Methods: The design of this study was quasi-experimental with a pretest-posttest design without control group design. A total of 62 toddlers were selected as samples by purposive sampling method to be accompanied intensively for 30 days Nutrition assistance activities include group education of nutrition, education and personal motivation, and cooking together to prepared healthy food and snacks used available ingredients. Results: The results showed that there increasing knowledge of mothers (p-value 0,000), there increasing intake of toddlers but not significantly different based on statistical tests, and there increasing nutritional status for toddlers based on weight-for-age and height-for-age indexes (p-value 0,02 and 0,004)The results of the correlation test showed that increasing protein intake had a significant correlation with an increase body weight and height of toddlers with p-value 0,003 and 0,002, while increasing fat intake had a significant correlation with an increase height of toddlers (p-value 0,001) Conclusions: Intensive nutritional assistance carried out for 30 days can improved the knowledge of mother’s with a p-value 0,000 and can improved the nutritional status of toddlers based on weight-for-age and height-for-age indexes with p-values 0,02 and 0,004.